CYTOGENETIC PRENATAL DIAGNOSIS ON 66 CHORIONIC VILLUS SAMPLES IN IRAN - P. Mehdipour (Iranian Journal of Public Health, 1992)
A total number of 66 chorionic villus samples were cytogenetically investigated. The samples consisted of 30 experimental cvs from spontaneously aborted materialand 36 from live gestations.80% of the samples were successfully grown, of the 30 cases 40% (12) and 33% (10)contained a normal female and a normal male karyotype, respectively, 3.3% (1) and3.3% (1) had abnormal karyotypes (47,XX, + 21; 47, XY, + 18), respectively, and 16% (6) of the cultures did not grow of the 36 CVS, 80. 5% of the trophoblasts grew. 50% and 30.5% had normal karyotypes with 46, XY and 46, XX chromosome constitutions respectively, of those with a male karyotype, one case was revealed to have two mitoses with 47+Xy, +21 karyotype and was considered to be a Mosaic with a minor abnormal clone. One case (2.7%) was a twin; 5.5% of the samples did not grow and 11.1% of the villi were inadequate. No serious complications occurred after CVS. 12 girls and 9 biys were delivered at term and cytogenetic findings on the CVS were postnatally confirmed for normal cases and even for a Mosaic case.